Amblyopia among Junior High School Students - Kuntadi Wahyu Widadi; Suhardjo Suhardjo; Hartono Hartono (Majalah Oftalmologi Indonesia, 2015)
Background: To determine the prevalence of amblyopia and correlation between the type of refractive error with the incidence of amblyopia on junior high school students in Yogyakarta Special Province. Methods: A cross-sectional study was conducted on one school in each district/city in Yogyakarta Special Province. All students underwent visual acuity, anterior segment and fundus examination. Best corrected visual acuity test was done on students with decreased visual acuity. Crowding phenomenon, neutral density filter, and eyeball alignment test were done on suspected amblyopic students. Amblyopia was defined if corrected visual acuity â‰¤6/12 or less in one or both eyes, or the difference of at least two best corrected visual acuity lines, without organic pathology. Results: A total of 1,664 students were examined, 1,590 were analyzed, 773 (48.6%) boys, 817 (51.4%) girls. There are 1,272 (80%) emetropia, 308 (19.4%) refractive errors, 1 (0.1%) anterior segment abnormality, 9 (0.6%) posterior segment disorders. On refractive error students obtained 359 (62.4%) eyes myopia, 2 (0.3%) eyes hyperopia, and 214 (37.2%) eyes astigmatism. Amblyopia prevalence was 1.07% (17 of 1,590 students), 8 (47.0%) boys and 9 (53.0%) girls. Astigmatism significantly affect the incidence of amblyopia, odds ratio 10.959 (95% CI: 3.189 to 37.667). The axis of astigmatism cylinder has no effect on the incidence of amblyopia. Anisometropia significantly affect the incidence of amblyopia, odds ratio 13.109 (95% CI: 4.618 to 37.208). Conclusion: Amblyopia prevalence on junior high school students in Yogyakarta Special Province was 1.07% with astigmatism and anisometropia influenced the occurrence. Keywords: Amblyopia, prevalence, refractive error, astigmatism, anisometropia